BAKIR VE NİKEL AMORF METALLERİNİN TERMODİNAMİK KARARLILIĞININ MOLEKÜLER DİNAMİK YÖNTEMLE İNCELENMESİ - GÜRBÜZ, YAVUZ (Fırat Üniveristesi, 2012)
Bu çalışmada, amorf maddelerin genel özelikleri incelenmiş, teknolojideki yeri ve önemine değinilmiştir. EAM yöntemi kullanılarak moleküler dinamik simülasyon vasıtasıyla sıvı bakır ve nikel 10^12 K/s , 10^13 K/s , 10^14 K/s soğutma hızları ile soğutulup simulasyon yoluyla amorf bakır ve nikel üretilmiştir. Üretilen amorf bakır ve nikel 100 K, 200 K, 300 K ve 400 K sıcaklıklarında 2.10^(-9) s bekletilmiştir. 2.10^(-9) bekletilen amorf bakır ve nikelin kristalleşme davranışları incelenerek zamana karşı kararlılığı tespit edilmiştir. Ayrıca, amorf bakır 100 K'den 1390 K'e kadar, nikel 100 K'den1820 K'e kadar 30 K sıcaklık artışları ile ısıtılarak amorf bakır ve nikelin termal kararlılığı belirlenmiştir.Çalışma sonucunda, sıvı nikel ve bakırı amorf hale dönüştürmek için 10^13 K/s ve daha büyük soğutma hızlarının gerektiği görüldü. Soğutma hızı artıkça oluşan amorf yapının zamana karşı kararlılığının daha büyük olduğu belirlendi. Büyük soğutma hızıyla oluşturulan amorf bakır ve nikelin termal kararlılığının daha yüksek olduğu gözlendi. Nikelin termal kararlılığının bakırın termal kararlılığından daha büyük olduğu görüldü.

In this study, general properties of amorphous substances were made and the importance in technology of this substances were mentioned. Using the EAM method , by means of molecular dynamics simulations , liquid copper and nickel were cooled with cooling rates of 10^12 K/s , 10^13 K/s , 10^14 K/s in order to produce the amorphous copper and nickel. Produced amorphous copper and nickel were kept for 2. 10^(-9) s at 100 K, 200 K, 300 K, 400 K temperatures. The structural stability against time of amorphous copper and nickel for a time period of 2. 10^(-9) s was determined taking into account crystallisation. In addition, while amorphous copper was heated from 100 K to 1390 K with temperature increment of 30 K and amorphous nickel was heated from 100 K to 1820 K with the same temperature increments, thermal stability of the amorphous copper and nickel were determined.According to the findings, it has been determined that at least 1013 K/s or more temperature rates are needed in order to obtain amorphous nickel and copper. Also, it has been found that, as increasing in the temperature rates both the thermal stability of the models and time stability increase. In addition, it has been shown that the stability of amorphous nickel is higher than amorphous copper.
Investigation of thermodynamic stability for copper and nickel amorphous metals by means of molecular dynamics method
Keywords: Fizik ve Fizik Mühendisliği